PEMEROLEHAN BAHASA PERTAMA SEBAGAI DASAR PEMBELAJARAN BAHASA KEDUA (Kajian Psikolinguistik) - Alam Budi Kusuma (STAI Masjid Syuhada Yogyakarta, 2016)
This article aims to describe the process of language development. Efforts made the linguist and psychologist in studying the problems of language learning from a variety of viewpoints and the theory is that a lot of benefits for language development so that today we can enjoy the results of studies on the language more familiar with psycholinguistics. There are two processes that occur when a person obtains his first language, which is a process of competence and performance process. These processes are different processes, competence is the process of mastery of grammar (phonology, Jurnal Komunikasi dan Pendidikan Islam, Volume 6, Nomor 2, Desember 2016 117 Alam Budi Kusuma : Pemerolehan Bahasa Pertama morphology, syntax and semantics) unconsciously. It needs to be questioned is how the strategy of the child in gaining his first language and whether each child has the same strategy in gaining his first language